A Case of Systemic Lupus Erythematosus and Antineutrophil Cytoplasmic Antibodies-Associated Vasculitis Overlap Syndrome - Hounoki, Hiroyuki; Shinoda, Koichiro; Matsui, Atsushi; Okumura, Maiko; Yamaguchi, Satoshi; Kakeshita, Kota; Yamazaki, Hidenori; Koike, Tsutomu; Makino, Teruhiko; Tobe, Kazuyuki (Case Reports in Rheumatology, 2021)
An overlap of systemic lupus erythematosus (SLE) and antineutrophil cytoplasmic antibodies- (ANCA-) associated vasculitis (AAV) is extremely rare: approximately 40 cases have been reported to date. A literature review indicates that they are more common in women in their forties, and simultaneous onset has been reported in 69% of cases. In addition, both lupus nephritis and ANCA-associated glomerulonephritis were observed on renal biopsy. This report presents the case of a 35-year-old woman with an 8-month history of polyarthralgia who was admitted to our hospital. She was diagnosed with SLE due to typical clinical presentation of the disease: polyarthritis, lymphocytopenia, hypocomplementemia, presence of antinuclear and anti-dsDNA antibodies, and proteinuria. However, purpura were scattered, and the titer of antimyeloperoxidase-antineutrophil cytoplasmic antibodies (MPO-ANCA) was high. A skin biopsy revealed leukocytoclastic vasculitis that involved poor immune complex deposition. A renal biopsy showed necrotizing glomerulonephritis with cellular and fibrocellular crescent formation that involved deposition of IgM and C3c only in the mesangial area and the peripheral capillaries. Additionally, no electron-dense deposits were observed under electron microscopy. These pathological findings were consistent with AAV rather than with SLE. Therefore, we finally diagnosed the patient with both SLE and microscopic polyangiitis. After treatment with methylprednisolone and intravenous cyclophosphamide pulse therapies, renal function improved and MPO-ANCA levels decreased. In cases of suspected overlap between SLE and AAV, appropriate diagnosis and treatment are important.